BLOOD VISCOSITY AND GIT DISORDERS OF HCV PATIENTS - Mubark, Nawras Najah; Rasha Ibrahim Salman; Shahad Q. Al-Hamadiny (Journal of Medical Genetics and Clinical Biology, 2024)
Background: Hepatitis C virus (HCV) infection is a blood-borne viral illness responsible for significant morbidity and mortality all over the world. The current study aims to determine the role of HCV in increasing blood viscosity that is accompanied by attacks and serious heart disorders, in addition to knowing the effect of this infection on irritations and disorders of the digestive system. Methods: The practical side included collecting blood samples from 50 HCV infected persons and 50 healthy persons as a control group. Laboratory and clinical tests were carried out at Al-Diwaniyah General Teaching Hospital, where HCV was determined by checking for antibodies using the ELISA test, while blood viscosity was determined by knowing the percentage of red blood cells (hemocrit) as part of the complete blood test. Gastrointestinal tract (GIT) diseases were diagnosed using gastroendoscopy and x-rays, in addition to investigations Helicobacter pylori (H. pylori). Result: ulcers and stomach acidity with colitis together (A,B,D) were in high rates in patients (58%) compared with healthy people (6%) and produced this is a clear statistical difference (p<0.05). Moreover, Blood viscosity increased (71.54%) with a rise titer of HCV in patients blood (18.38 logIU/mL) that associated with appearance of strong positive linear correlation (r= 0.965, p= 0.004). In conclusion: HCV leads to serious complications, especially the digestive system and circulation, and the risk of these disorders increases with the increased survival of the virus C in the patient's liver. Therefore, it is necessary to use appropriate treatments, especially effective modern treatments represented by Harvoni.